Experiences From the Field: Transforming Teaching and Learning Through Child Rights Education - Mreiwed, Hala (Journal of the Canadian Association for Curriculum Studies, 2020)
Children are not just the future; they are the present. Their voices must be heard and their rights fully implemented in the here and now. Empty promises for future actions do not build communities but destroy momentum. It is therefore essential that children learn about their rights, and for these rights to be at the core of teaching. Through reflective writing, I explore my personal and professional experiences as an educator, course lecturer, researcher and Child Rights Education (CRE) consultant in learning and teaching about the UN Convention on the Rights of the Child (CRC) while working in Canada and abroad for over a decade. Personal reflections from workshops, trainings and desk research have led to the understanding that it is essential for children to learn about their rights and for teachers to be trained in CRE to transfer this knowledge. This process of knowledge transfer can help educators and learners transform the CRC from a symbolic text to a living document, ensuring that child rights are lived (experienced) and living (contextualized and adapted to present and emerging needs), ultimately bridging diversities, leading to equitable practices and fostering understanding, respect and inclusion in and beyond the classroom walls. Informing the research findings are a conversation about child rights, an understanding of the constructed nature of childhood, and the role of creative drama as a pedagogical approach in transferring knowledge and opening the path for creative and collaborative practices and forms of inquiry in CRE.